Improving Reproductive Performance and Health of Mammals Using Honeybee Products - Nesrein M. Hashem; Eman M. Hassanein; Jesus Simal-Gandara (MDPI AG, 2021)
Honeybee products have positive effects on the reproductive performance of mammals. Many honeybee product constituents are biologically active, with antioxidant, antimicrobial, antiviral, anti-inflammatory, immunomodulatory, antifungal, wound-healing, and cardio-protective properties. Honeybee products also improve male and female fertility rates by enhancing gamete cryopreservation, in vitro maturation and fertilization, and embryo development. Previously published studies confirmed their efficacy for alleviating reproductive toxicity caused by contaminants and lifestyle habits that impair overall health and well-being. However, high-dose oral administration of honeybee products may adversely affect the reproductive system, and unfavorable effects were alleviated by treatment cessation. For this reason, this review proposes that bioactive components from bee products can be used as a strategy for improving the reproductive performance and health of mammals.